Strong Association Between In-Migration and HIV Prevalence in Urban Sub-Saharan Africa - Voeten, Hélène A. C. M. (2010)
BACKGROUND: Enormous variation exists in HIV prevalence between countries in sub-Saharan Africa. The contribution of migration to the spread of HIV has long been recognized, but its effect at the population level has never been assessed. In this ecological analysis, we explore how much variation in HIV prevalence in urban sub-Saharan Africa is explained by in-migration. METHODS: We performed a linear regression to analyze the association between the proportion of recent in-migrants and HIV prevalence for men and women in urban areas, using 60 data points from 28 sub-Saharan African countries between 1987 and 2005. RESULTS: We found a strong association between recent in-migration and HIV prevalence for women (Pearson R(2) = 57%, P < 0.001) and men (R(2) = 24%, P = 0.016), taking the earliest data point for each country. For women, the association was also strong within east/southern Africa (R(2) = 50%, P = 0.003). For both genders, the association was strongest between 1985 and 1994, slightly weaker between 1995 and 1999, and nonexistent as from 2000. The overall association for both men and women was not confounded by the developmental indicators GNI per capita, income inequalities, or adult literacy. CONCLUSIONS: Migration explains much of the variation in HIV spread in urban areas of sub-Saharan Africa, especially before the year 2000, after which HIV prevalences started to level off in many countries. Our findings suggest that migration is an important factor in the spread of HIV, especially in rapidly increasing epidemics. This may be of relevance to the current HIV epidemics in China and India.